PRAGMATIC TRANSFER IN REFUSALS REALIZED BY PROFICIENT EFL LEARNERS ENGLISH EDUCATION PROGRAM SRIWIJAYA UNIVERSITY - NFN Eviliana (MABASAN, 2015)
This research was aimed at describing the strategies of proficient EFL students’ refusal realization in Indonesian and in English and the occurrences of pragmatic transfer (PT) in their refusal realization. Qualitative research method was employed. As the subsidiary of the qualitative research method, quantitative research method was also employed. The subjects were 18 EFL students of English Study Program Sriwijaya University whose TOEFL prediction scores were 450 above. DCT was used as the instrument of collecting data. Data were analyzed based on combined refusal classification by Wannaruk (2005) and Campillo (2009). The results of this research show that proficient EFL students’ mostly used the indirect strategies in their refusal realization both in English and Indonesian. Nevertheless, differences occurred in term of semantic formula choice and order in the twelve situations of DCT. Thus, PT could be observed. In consequences, it is suggested to foreign language teacher or lecturers should be aware that fluency in a language involves both a mastery of linguistic knowledge and pragmatic knowledge. Foreign language learners should be aware of the fact that social variables play a role when refusing, and that their inappropriate refusals may make them sound rude, vague or abrupt. Due to the limitation of this study, future researchers should also explore the differences between EFL  students’ refusal realization in their mother tongue  and Indonesian, the idiosyncrasies that occur in  the proficient EFL students’ refusal realization, and communication strategies used by EFL students in realizing their refusals.